2017
DOI: 10.1038/s41598-017-13438-5
|View full text |Cite
|
Sign up to set email alerts
|

Turnover and flow of the cell membrane for cell migration

Abstract: The role of cell membrane dynamics in cell migration is unclear. To examine whether total cell surface area changes are required for cell migration, Dictyostelium cells were flattened by agar-overlay. Scanning electron microscopy demonstrated that flattened migrating cells have no membrane reservoirs such as projections and membrane folds. Similarly, optical sectioning fluorescence microscopy showed that the cell surface area does not change during migration. Interestingly, staining of the cell membrane with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

13
77
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(90 citation statements)
references
References 54 publications
(55 reference statements)
13
77
0
Order By: Relevance
“…Interestingly, in this study a direct relationship between cell migration and membrane turnover rate was observed, suggesting that the cells establish a fluid drive that contributes to the generation of force required for motility, as suggested previously (4). Importantly, it appears that myosin and actin have only a supporting function in the establishment of the fluid drive, since treatment with actin-or myosin-disrupting drugs, such as latrunculin B or blebbistatin, did not significantly affect membrane movement (10). In good agreement, retrograde membrane flow in apicomplexan parasites is not strictly dependent on parasite actin, as shown for Plasmodium sporozoites and Toxoplasma tachyzoites (7,11).…”
Section: Introductionsupporting
confidence: 74%
See 2 more Smart Citations
“…Interestingly, in this study a direct relationship between cell migration and membrane turnover rate was observed, suggesting that the cells establish a fluid drive that contributes to the generation of force required for motility, as suggested previously (4). Importantly, it appears that myosin and actin have only a supporting function in the establishment of the fluid drive, since treatment with actin-or myosin-disrupting drugs, such as latrunculin B or blebbistatin, did not significantly affect membrane movement (10). In good agreement, retrograde membrane flow in apicomplexan parasites is not strictly dependent on parasite actin, as shown for Plasmodium sporozoites and Toxoplasma tachyzoites (7,11).…”
Section: Introductionsupporting
confidence: 74%
“…During motility, most eukaryotic cells show a capping activity of surface ligands, which is dependent on actin, microtubules, and a secretory-endocytic cycle, leading to the establishment of a retrograde membrane flow (4,9). A recent study on Dictyostelium provided direct evidences for the fluid flow model during cell migration (10). This study demonstrated that, during migration of Dictyostelium, the membrane volume of the cell remains constant due to the occurrence of a secretory-endocytic cycle.…”
Section: Introductionmentioning
confidence: 61%
See 1 more Smart Citation
“…According to the Glideosome model, the force generated for motility and invasion relies exclusively on F‐actin polymerised at the apical tip of the parasite by the action of Formin‐1 and translocated within the narrow space (~30 nm) between the IMC and PM of the parasite . However, recent studies suggest that the parasite can also use other motility systems, such as a secretory‐endocytic cycle that produces retrograde membrane flow , similar to the fountain flow model suggested for other eukaryotes .…”
Section: Introductionmentioning
confidence: 96%
“…In the postnatal RMS, neuroblasts travel in chains ensheathed by astrocytic processes along blood vessels (Kaneko et al, 2010;Snapyan et al, 2009;Whitman et al, 2009). Cell migration is a very dynamic process composed of migratory phases intercalated with stationary periods and is accompanied by structural remodeling, organelles dynamic and protein trafficking and turnover (Tanaka et al, 2017;Webb et al, 2002). Cell migration also entails a considerable bioenergetic demand, and it is still unclear how migrating cells regulate cellular homeostasis by clearing damaged organelles and aggregated/misfolded proteins, and how the metabolic requirements of neuroblasts are dynamically regulated during the different phases of cell migration.…”
Section: Introductionmentioning
confidence: 99%